Must-see musicals : 50 show-stopping movies we can't forget - Barrios, Richard (Running Press, 2017)
"Spanning nine decades and showcasing the most memorable songs, dazzling dancing, and brightest stars ever to grace the silver screen, Must-See Musicals is the guide to the greatest musicals of all time from the most trusted authority on film: Turner Classic Movies."--Publisher's description.